Does sector matter for the quality of care services? A secondary analysis of social care services regulated by the Care Inspectorate in Scotland. Issue 2 (15th February 2019) - Bach-Mortensen, Anders Malthe; Montgomery, Paul
Abstract : Objectives: Social services are increasingly commissioned to third and for-profit sector providers, but little is known about whether and how these changes influence quality indicators. We assessed quality-related outcomes across for-profit, public and third sector organisations delivering social care services. Design: A secondary analysis was conducted on publically available data collected by the independent regulator of social care organisations in Scotland. All outcomes are reported as predicted probabilities derived from multivariate logistic regression coefficients. Generalised ordered logit models are utilised for the quality domains and the risk assessment score and logistic regression for whether complaints or requirements were issued to organisations. Setting: Organisations inspected by the Care Inspectorate in Scotland. Population: 13 310 social care organisations (eg, nursing homes and day care organisations). Primary outcomes: The quality and risk domains collected by the Care Inspectorate and complaints and requirements issued to organisations within the last 3 years. Results: Controlling for multiple factors, we find that public and third sector providers performed consistently and statistically significantly better than for-profit organisations on most outcomes. For example, for-profit services were the most likely to be rated as high and medium risk (6.9% and 13.2%, respectively), and the least likely to be classified as low risk (79.9%). Public providers had the highest probability of being categorised as low risk (91.1%), and the lowest probability of having their services classified as medium (6.9%) and high risk (2%), followed by third sector providers (86%, 8.5% and 4.5%, respectively). Public providers performed better than third sector providers in some outcomes, but differences were relatively low and inconsistent. Conclusion: Public and third sector providers were rated considerably higher than their for-profit counterparts on most observed outcomes. Regulators might use this information to consider how social care providers across sector are incentivised to manage their resources.